Morphometrical and Gross anatomical Study on the Sternum of Blue and Gold winged Macaw (Ara ararauna) - Yousuf Dar (Indian Journal of Veterinary Anatomy, 2022)
The present study was conducted on the sternum of blue and gold winged macaw.The sternum of macaw consisted of rostrum (manubrium sterni), body (corpus sterni) and sternal crest (crista sterni). The manubrium sterni was hook like, flattened from side to side. The corpus sterni was long 76.35 mm quadrilateral with concave dorsal and convex ventral surface. It presented four borders; anterior, posterior and two lateral borders.The width of sternum between the craniolateral process was 33.89 mm and the width at caudal aspect was 49.21mm. The width of sternum at the anterior aspect was less than the width at the posterior aspect.In the present study the dorsal surface was concave and showed a groove in the center extending from behind the cranial border up to distal third. The concavity was more in cranial half and nearly flat in caudal half.Numerous foramina were present on the anterior two third of the dorsal surface. The ventral surface was convex and presented a large, boat shaped sternal crest along its median line.The sternal crest was located at the center of the ventral surface of corpus sterni. The sternal crest was boat shaped and 89.05 mm in length. The height of the sternal crest along with the cranial border was 27.93 mm. Therefore, it was concluded that the sternum of blue winged macaw was similar to goose and pigeon and hence the morphometry and morphology of sternum is suitable for the flying of bird.